Chapter «A quei tempi». Spagnolismo e teatro all'italiana. Miti e stereotipi - PIERMARIO, VESCOVO (Studi e saggi, 2020)
The contribution concerns the relationship between Pietro Napoli Signorelli, his Storia critica de' teatri antichi e moderni (Critical history of ancient and modern theaters), and the defense of Spanish literature by the Jesuit Francisco Saverio Lampillas, and the answer in Critical essay which Pietro Napoli Signorelli published in 1783. An Italian who spent a large period of his life in Spain and a Spaniard who lives and writes in Italy offer an observation point of extraordinary importance, almost a cross-reflection of the ideas and clichés of "Spanishism" and "Italianism" that had dominated the 18th Century. The critique of "Spanishism" and the long distance from the siglo de oro, from the triumph of metaphor and irregularity, in relation to the critique of what begins to be called the "commedia dell'arte", shows, at the turn of the century, just beyond the defense of the respective traditions and the positions of the two contenders, a change taking place of great depth that is announced on the European cultural scene, transforming the horizons of controversy into renewed myths.